Konotativnost vybraných skupin partnerských pojmenování - Štěpánová, Pavla (My University, 2016)
The presented article defines the term partners´ name and emphasizes the emotional and characteritazional function. More it deals with connotational function which enable the non-linguistic character´s interpretation of the numerous partners´ name´s origin. Connotations are described on the basis of the phraseology and short psychological, anthropological backround of partnership. In compliance with cognitive conception of the metaphor, two main partners´ conceptualizations are presented (partner is preciousness and partner is the subject/object of desire). These also constitute partial connotations (e.g. partner is physical contact, or partner is part of human body etc.)
Keywords: Czech language, partners´ name; connotational function; conceptualizations